Efficacy and safety of caspofungin for the treatment of invasive pulmonary aspergillosis in patients with chronic obstructive pulmonary disease - Shaoqiang Li; Zhengtu Li; Penglei Wang; Yangqing Zhan; Jiaxing Xie; Feng Ye (Journal of International Medical Research, 2024)
Objectives We assessed the efficacy of a 3-week primary or salvage caspofungin regimen in patients with chronic obstructive pulmonary disease (COPD) and concomitant proven or suspected invasive pulmonary aspergillosis (IPA). Methods Forty-four patients were treated with an initial loading caspofungin dose of 70 mg, followed by a daily dose of 50 mg for 20 days. The main efficacy endpoint was clinical effectiveness. Secondary endpoints included the clinical efficacy of caspofungin after 1 week, therapeutic efficacy based on the European Organization for Research and Treatment of Cancer and Mycoses Study Group Education and Research Consortium (EORTC/MSG) criteria, the sensitivity of different Aspergillus strains to caspofungin in vitro , and the safety of caspofungin. Results An assessment of 42 patients in the intention-to-treat group revealed efficacy rates of 33.33% within 1 week and 38.10% within 3 weeks. According to the EORTC/MSG criteria, the treatment success rate was 38.10%. The success rate of first-line treatment was 54.76%, whereas salvage treatment had a success rate of 45.24%. No adverse events were reported among the participants. Conclusions Caspofungin is effective and safe as an initial or salvage treatment for patients with IPA and COPD.